Renormalization of generalized scalar Duffin-Kemmer-Petiau electrodynamics - Bufalo, R.; Cardoso, T. R.; Nogueira, A. A.; Pimentel, B. M. [UNESP] (American Physical Society (APS), 2018)
We establish the multiplicative renormalization procedure of generalized scalar Duffin-Kemmer-Petiau electrodynamics (GSDKP4) in the mass shell. We show an explicit calculation of the first radiative corrections (one-loop) associated with the photon propagator, meson propagator, vertex function, and photon-photon four-point function utilizing the dimensional regularization method, where the gauge symmetry is manifest. As we will see, one of the consequences of the study is that, from the complete photon propagator renormalization condition, imposing that it behaves as a massless field, an energy range where GSDKP4 is well defined is m2 k2<mp2, by evaluating the effective coupling constant. From the complete DKP propagator, we will present two ways of evaluating the renormalizaton conditions for the pole and residue, due to DKP trilinear algebra. We will also see that the DKP algebra ensures that the Ward-Fradkin-Takahashi (WFT) identities in the first radiative corrections of the vertex and photon-photon four-point function prohibit UV divergences. Furthermore, in order to show the effectiveness of the renormalization procedure on the present theory, a diagrammatic discussion of the photon self-energy and vertex part at α2 order is presented.